Removal and recovery of phosphorus from municipal wastewaters using a ferric nanoparticle adsorbent - Martin, Benjamin D. (Cranfield University, 2010)
Phosphorus is removed from wastewater streams to prevent the ecologically harmful effects of eutrophication in receiving natural systems. Current chemical and biological techniques for removing phosphorus from wastewater are not able to practicably achieve the new discharge limit expected under the Water Framework Directive of 0.1 mg phosphorus L- 1 . In addition, they do not represent an economically viable route for the recovery and reuse of the phosphorus they remove. Cont/d.